Entre o desejo manifesto de criança e a viabilidade da adoção: um estudo psicanalítico sobre motivações inconscientes que obstam o processo adotivo - Gimenes, Fernanda Moraes Andrade (2016)
This is a descriptive, qualitative reserch based on a psychoanalytical approach concentrating on documentary and bibliographic study. It aims to identify and reflect on the most recurrent emerging unconscious motivations during the psychological evaluation process of applicants for adoption in 2014, in a Court of Childhood and Youth of a District of the State of São Paulo that made it impossible, at least temporarily, the adoptive process and resulted in: 1) Routing for psychotherapy or to an adoption support group prior to reevaluation; 2) Psychological unfavorable opinion; 3) Process suspension tip; 4) Withdrawal; 5) Decline/ refusal of the adoption by the applicant at the time of presentation of the child to be adopted; 6) Child back durind living stage or after the legalization of adoption. Aimed at building bases to support greater accuracy in the evaluation standards, listening to the judicial psychologists through the recognition of unconscious motivations representing predictors or risk factors to avoid unsuccessful adoptions. Therefore, this study was conducted in three stages: 1) Documentary examination of the file and psychological advice; 2) Bibliographic study; 3) Reflection on the findings, relating them to literature. It was used the psychoanalytic method and contente analysis according to Bardin (1977), for the treatment of qualitative data. The results showed, in a general way, the relevance of defense mechanisms as infeasibiliting adoption factors in 2014, among which mainly adoption as reative formation, the idealizacion of adoption and of the child and the projection aspects of the applicants on the child. The bereavement not prepared, especially those related to the child genetic heritage, as well as other sons deathes, also stood out. It was made clear, how much an adoption, not rarely, shows to be a solution to problems related to infertility and how a child demand, many times, means not more than a will, been far from an unconcios desire. The data show the relevance of need for some candidates to adoption to submit to previous psycological interventions